THE IMPACT OF INFLATION ON THE STANDARD OF LIVING IN DEVELOPING COUNTRIES - Khalilova Nilufar Ahmatovna; Marifjanova Kamola Sherbek qizi (Scholar Express Journals, 2025)
Inflation is a persistent rise in the general price level of goods and services, which, while being a natural part of economic dynamics, poses significant risks when it becomes uncontrolled—particularly in developing countries. This paper explores the root causes, socio-economic consequences, and policy responses to inflation in developing nations. It emphasizes the structural nature of inflation, its effects on purchasing power, food security, and social inequality. By analyzing case studies from Venezuela, Turkey, and Uzbekistan, this study identifies patterns in inflationary dynamics and presents a set of recommendations aimed at mitigating its impact on the most vulnerable segments of society. The study concludes that sustainable control of inflation requires a systemic and multi-sectoral approach involving both macroeconomic stabilization and social protection policies.
Keywords: inflation; developing countries; standard of living